An empirical analysis of corporate legitimacy through corporate responsibility activities among Government Linked Companies (GLCs): the influences of special interest groups / Mahadir Ladisma @ Awis - Ladisma @ Awis, Mahadir (Institute of Graduate Studies, UiTM, 2016)
Corporate social responsibility (CSR) is one of the new corporate governance mantras that give some credence to stakeholder theory of corporations. Studies have examined the interest in, levels and effects of CSR investments on employees, customers, investors etc. However, CSR is an intermediate outcome. Corporate legitimacy is what corporations seek to achieve through CSR although this is not always explicit. This study examines the relationship between corporate responsibility and corporate legitimacy. Secondly, corporate responsibility intensity and types of corporate responsibility activities have been examined from the standpoint of shareholders, customers, employees and other groups closely linked to the businesses. These are undoubtedly sections of society but they are role restricted groups. This study examines the less role restricted special interest groups (SIGs) that represent and/or speak on behalf of the various components of the society. The study focused on 17 publicly listed Government Linked Corporations (GLCs) which are pressured by their owner – the government, to be socially sensitive and responsible in their business activities. The three main aims of the study are: (i) to determine the level of corporate legitimacy perceptions of GLCs in the eyes of SIGs as proxies for society (special interest groups); (ii) to examine whether and which type of corporate responsibility activities of GLCs influence their corporate legitimacy perceptions; and (iii) to find out the extent to which the SIGs characteristics moderate the relationship between corporate responsibility activities and corporate legitimacy of GLCs…